Life expectancy in metastatic urothelial bladder cancer patients according to race/ethnicity - Chierigo, Francesco; Borghesi, Marco; Würnschimmel, Christoph; Flammia, Rocco Simone; Horlemann, Benedikt; Sorce, Gabriele; Hoeh, Benedikt; Tian, Zhe; Saad, Fred; Graefen, Markus; Gallucci, Michele; Briganti, Alberto; et al. (International urology and nephrology, 2022)
PURPOSE: to compare observed overall survival vs age-adjusted lifetable (LT) derived life expectancy (LE) in metastatic urothelial bladder cancer (MBCa) patients according to race/ethnicity. METHODS: We identified Caucasian, African American, Hispanic/Latino and Asian metastatic urothelial bladder cancer patients from 2004 to 2011 within the Surveillance, Epidemiology and End Results database. Social Security Administration tables were used to compute 5 year LE. LT-derived LE was compared to observed overall survival OS. Additionally, we relied on Poisson regression plots to display cancer-specific mortality (CSM) relative to other-cause mortality (OCM) for each race/ethnicity. RESULTS: Overall, 2286 MBCa patients were identified. Of those, 1800 (79%) were Caucasian vs 212 (9.3%) African American vs 189 (8.3%) Hispanic/Latino vs 85 (3.7%) Asians. The median age at diagnosis was 71 years for Asians vs 70 for Caucasians vs 67 for Hispanic/Latinos vs 67 for African Americans. African Americans showed the biggest difference between observed OS and LT-predicted LE at five years (- 83.8%), followed by Hispanic/Latinos (- 81%), Caucasians (- 77%) and Asian patients (- 69%). In Poisson regression plots, Hispanic/Latinos displayed the highest cancer-specific mortality rate (88%), while African/Americans showed the highest other cause mortality rate (12%). Conversely, Asian patients displayed the lowest CSM rate (83%) and second lowest OCM rate (7%). CONCLUSIONS: African Americans showed the least favorable survival profile in MBCa, despite being youngest at diagnosis. Contrarily, Asians displayed the best survival profile in MBCa, despite being oldest at diagnosis.
Keywords: SEER Program; Black or African American; Life Expectancy; Life expectancy; Social security administration; Metastatic bladder cancer; karcinom z přechodných buněk; nádory močového měchýře; Surveillance; běloši; program SEER; Ethnicity; White People; černoši nebo Afroameričané; lidé; Humans; etnicita; naděje dožití; Urinary Bladder Neoplasms; SEER; Life table; Carcinoma, Transitional Cell